2016
DOI: 10.1111/imb.12212
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and gene‐silencing of a putative odorant receptor transcription factor in Varroa destructor: possible role in olfaction

Abstract: The ectoparasitic mite Varroa destructor is one of the major threats to apiculture. Using a behavioural choice bioassay, we determined that phoretic mites were more successful in reaching a bee than reproductive mites, suggesting an energy trade-off between reproduction and host selection. We used both chemo-ecological and molecular strategies to identify the regulation of the olfactory machinery of Varroa and its association with reproduction. We focused on transcription regulation. Using primers designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…The strong association between the Varroa’s and the bee’s life cycles underscores the importance of Varroa chemical perception for its host finding, selection and reproduction 20,22,23 . Recently we found that phoretic mites are significantly more successful in reaching an adult bee host 24 , and identified a gene transcript for pheromone receptor transcription factor-like (PRTF-like), which is involved in Varroa chemosensing and host finding behavior. Silencing this gene using RNA interference (RNAi), effectively converted a phoretic mite into a reproductive mite.…”
Section: Introductionmentioning
confidence: 99%
“…The strong association between the Varroa’s and the bee’s life cycles underscores the importance of Varroa chemical perception for its host finding, selection and reproduction 20,22,23 . Recently we found that phoretic mites are significantly more successful in reaching an adult bee host 24 , and identified a gene transcript for pheromone receptor transcription factor-like (PRTF-like), which is involved in Varroa chemosensing and host finding behavior. Silencing this gene using RNA interference (RNAi), effectively converted a phoretic mite into a reproductive mite.…”
Section: Introductionmentioning
confidence: 99%
“…The current RNAi protocol utilizes soaking the mites in a solution containing dsRNAs for delivery [4850] thus providing a means of delivery for laboratory experimentation but of limited potential for field applications. The feeding protocol described in this report establishes a means to deliver and assess similar systems and molecules where oral administration could contribute as an additional avenue of application.…”
Section: Discussionmentioning
confidence: 99%
“…Application of RNA interference (RNAi) has been achieved by soaking the mites in an 0.9% saline solution containing a double stranded RNA (dsRNA) sequence with return to a bee pupae has resulted in knockdown of mu-class glutathione S-transferase, B-type allatostatin, a member of the crustacean hyperglycaemic hormone (CHH), and pheromone receptor transcription factor (PRTF) [4850]. Alternatively, feeding of the Varroa mites to deliver biologicals has been less successful and has required some form of membrane such as stretched Parafilm [51, 52].…”
Section: Introductionmentioning
confidence: 99%
“…Supporting the importance of chemoreception in Varroa mites as they enter brood cells and switch from phoretic to reproductive, a recent study has found that the pheromone receptor transcription factor like (PRTF) is expressed much more abundantly in the forelegs of phoretic mites than of reproductive ones (Singh et al 2016). Phoretic mites with experimentally reduced levels o f P RT F ( t h r o u gh RN A i ) h a d we a k e r electrotarsogram responses to bee head space and took longer to find a host, but had induced vitellogenin levels (Singh et al 2016).…”
mentioning
confidence: 99%
“…Phoretic mites with experimentally reduced levels o f P RT F ( t h r o u gh RN A i ) h a d we a k e r electrotarsogram responses to bee head space and took longer to find a host, but had induced vitellogenin levels (Singh et al 2016).…”
mentioning
confidence: 99%